Pengelolaan Pajak Kendaraan Bermotor untuk Peningkatan Pendapatan Asli Daerah (PAD) di Kabupaten Lumajang - Yusuf Wibisono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
The management of motor vehicle tax to increase PAD in Lumajang Regency Entering the era of regional autonomy (Otoda) as it is now, the Regional Government is given extensive authority to carry out development programs and at the same time to realize community welfare. Funding for development programs in the area comes from various regional revenues. Among the sources of income are taxes. The tax that is excellent because it has great potential, positive and significant impact on the PAD is motor vehicle tax. The purpose of this study was to determine the development and contribution of motor vehicle tax to PAD in Lumajang Regency over the past two years. This study uses a qualitative descriptive approach, the research method uses interview methods and documentation. Also supported by a literature review that is relevant to the subject matter. From the results of the study, it is known that the management of motor vehicle tax in Lumajang Regency runs well and successfully surpasses the target every year. This is very useful to contribute to the PAD of Lumajang Regency. The strategies and policies pursued by the government to increase motor vehicle tax, among others, by improving the management of motor vehicle tax, both Human Resources (HR) and bureaucracy. Improve services with the use of technology and so on.